Construction planning and scheduling a case study of "Cadangan membina dan menyiapkan Kulliyyah Sains untuk Universiti Islam Antarabangsa Malaysia - Mohd Khalild, Abdul Kadir (2006)
Construction planning and scheduling is one of the important tool in a construction project. Every construction project involve with a lot of activities which need to be planned and schedule properly to ensure the completion of the project. Therefore the study on construction planning and scheduling must be conduct to provide knowledge on this topic and (a view on how it is be implement theoretically and in the real case of construction project). This study reviewed on the concept of sequence of work for building construction project, scheduling technique used in the primavera project planner and the development of construction planning and scheduling on building construction of science faculty International Islamic University Malaysia (HUM). From the study is found that the sequence of work for building construction project can be divided in to four main categories which is substructure work, superstructure work, architectural work and mechanical and electrical work. The study also found that the precedence diagramming method PDM is a scheduling technique used in the primavera project planner and the total duration for the HUM project after developed using the primavera project planner is 695 days.